Electrocardiographic and cardiometabolic risk markers of left ventricular diastolic dysfunction in physically active adults: CHIEF heart study - Liu, Pang-Yen; Tsai, Kun-Zhe; Huang, Wei-Chun; Lavie, Carl J.; Lin, Gen-Min (Frontiers in Cardiovascular Medicine, 2022)
Aims This study was aimed to investigate the associations of the cardiometabolic and ECG markers with left ventricular diastolic dysfunction (LVDD) in physically active Asian young adults, which have not been clarified in prior studies. Methods and Results A total of 2,019 males, aged 18-43 years, were included from the military in Taiwan. All subjects underwent anthropometric, hemodynamic and blood metabolic markers measurements. Physical fitness was investigated by time for a 3000-meter run. LVDD was defined by presence of either one of the three echocardiographic criteria: (1) the mitral inflow E/A ratio <0.8 with a peak E velocity of >50 cm/s, (2) the tissue doppler lateral mitral annulus e’ <10 cm/s, (3) the E/e’ ratio >14. Multiple logistic regressions with adjustments for age, physical fitness and pulse rate were used to determine the associations of the cardiometabolic and ECG markers with LVDD, respectively. The prevalence of LVDD was estimated 4.16% (N =84). Of the cardiometabolic markers, central obesity, defined as waist circumference ≥90 cm, was the only independent marker of LVDD [odds ratio (OR) and 95% confidence intervals: 2.97 (1.63-5.41)]. There were no associations for hypertension, prediabetes and dyslipidemia. Of the ECG markers, left atrial enlargement and incomplete right bundle branch block/ intraventricular conduction delay were the independent ECG markers of LVDD [OR: 2.98 (1.28-6.94) and 1.94 (1.09-3.47), respectively]. There were borderline associations for the Cornell-based left ventricular hypertrophy and inferior T wave inversion [OR: 1.94 (0.97-3.63) and 2.44 (0.98-6.08) respectively]. Conclusion In physically active Asian young male adults, central obesity and some ECG markers for left heart abnormalities were useful to identify LVDD.